Design, synthesis and molecular docking studies of imidazole and benzimidazole linked ethionamide derivatives as inhibitors of InhA and antituberculosis agents. (15th March 2022) - Raghu, M.S.; Pradeep Kumar, C.B.; Yogesh Kumar, K.; Prashanth, M.K.; Alshahrani, Mohammad Y.; Ahmad, Irfan; Jain, Ranjana
Graphical abstract: Highlights: Novel imidazole/benzimidazole-ethionamide conjugates was synthesized and characterized. Two compounds showed more potent than standard isoniazid. InhA appeared as an important target enzyme of the compounds. Top hit like compounds exhibit strong binding interactions with target InhA protein. In silico studies supported InhA inhibition assay. Abstract: To explore effective antituberculosis agents, a new class of imidazoles and benzimidazoles linked ethionamide analogs were designed and synthesized. The elemental analysis, 1 H NMR, 13 C NMR and mass spectral data were used to characterize all of the novel analogs. In vitro activity against Mycobacterium tuberculosis (Mtb) H37Rv was assessed for all of the target compounds. The hydroxy and nitrile moieties on the imidazole ring, as well as the hydroxy and methoxy groups on the benzimidazole ring connected to the ethionamide side chain, were shown to be advantageous. In our cell viability experiment against the Vero cell line, all of the compounds were non-cytotoxic even at 100 μM. To confirm the powerful analogs target identification, we investigated their in vitro inhibitory action on an M. tuberculosis InhA over-expressing (Mtb InhA-OE) strain, which yielded MICs nearly twice those of the Mtb H37Rv strain. Furthermore, the results of molecular docking confirmed the experimental findings. Additionally, the molecules were evaluated in silico for ADMET and drug similarity features. The experimental observation enables the newly generated ethionamide derivatives to be attractive candidates for the creation of newer and better anti-TB agents.